Effect of sea urchin human harvest in promoting canopy forming algae restoration. (5th April 2019) - Piazzi, L.; Ceccherelli, G.
Abstract: The ability of species to recover from disturbance through natural recruitment is an important factor in determining the resilience of assemblages. The identification of patterns of resilience compatible or favoured by human activities has become a compelling need to address environmental management. In marine coastal systems, barrens are characterized by a dominance of encrusting calcareous algae and by high density of sea urchins and are considered an alternative stable state of systems collapsed due to overgrazing by sea urchins that originally were dominated by canopy-forming macroalga. Sea urchins also represent an important commercial resource, as some species are exploited worldwide. The present study aims at evaluating the effect of the harvesting of the sea urchin Paracentrotus lividus on promoting the shift from barren towards macroalgal beds. Three treatments were considered within a manipulative experiment in a Cystoseira -barren mixed habitat: natural sea urchins density, removal of all sea urchins and removal of only commercial P. lividus (natural density of the non-harvested sea urchin Arbacia lixula and juvenile P. lividus are maintained). Results showed that the removal of commercial P. lividus can promote Cystoseira recruitment. In fact, even if both A. lixula and juvenile P. lividus were present, the barren area decreased due to the spread of fleshy algae and the recruitment of the Cystoseira from the edge of vegetated patches. Therefore, removal of commercial P. lividus urchin is inferred as a reliable strategy to return ecosystems dominated by canopy-forming macroalgae. Highlights: The study evaluated sea urchin harvesting on promoting macroalgal beds. A manipulative experiment was performed in a Cystoseira -barren mixed habitat. The removal of the commercial Paracentrotus lividus can promote macroalgal beds. The non-harvested Arbacia lixula did not prevent the recruitment of Cystoseira . Sea urchins management should be considered to recovery macroalgal canopy.